Lysozymes from natural rubber latex (Hevea brasiliensis): assay development and recovery using ammonium sulphate and surfactant precipitations - Seng, Yong Yee; Yun, Chen Tzi; Abdullah, Nurulhuda; Faizal Wong, Fadzlie Wong (Elsevier BV, 2021)
To date, the C-serum and the bottom fraction of natural rubber latex (NRL) are still generally being considered as waste. However, they are rich sources of lysozyme, which is a bacteriolytic enzyme that has huge potential for biotechnological exploitations. So far, there are no reports on lysozyme recovery for the valorisation of NRL by-products. Therefore, this study aimed to (1) develop and validate a lysozyme assay based on the lysoplate method using the cloudy NRL sample and Micrococcus lysodeikticus cells and (2) recover lysozyme from the NRL fractions using ammonium sulphate ([NH4]2SO4) precipitation (direct and fractional modes) and the novel sodium di-(2-ethylhexyl) sulfosuccinate (AOT) surfactant precipitation. The assay developed in this study was high in both accuracy (97.54%) and precision (13.61% relative standard deviation). The detection and quantification limits, as well as the linearity range of the assay were 0.13 U/mL, 0.04 U/mL and 0-10,445.40 U/mL, respectively. As for the lysozyme recovery from the C-serum of NRL, the performance of the AOT precipitation via negative mode (activity recovery [AR] = 67.29%; purification factor [PF] = 2.42) was comparable (p > 0.05) to that of (NH4)2SO4 precipitation (direct mode: AR = 88.44%, PF = 2.18; fractional mode: AR = 95.44%, PF = 3.05). Meanwhile, for the lysozyme recovery from the bottom fraction of NRL, the AOT precipitation (AR = 71.94%; PF = 1.73) was shown to be superior than (NH4)2SO4 precipitation (direct mode: AR = 25.68%, PF = 3.23; fractional mode: AR = 27.88%, PF = 12.87). Hence, considering its effectiveness, simplicity, rapidity, as well as its great potential to be integrated with rubber product manufacturing, the AOT precipitation is an attractive alternative recovery method for lysozyme recovery from NRL. The findings described herein are significant for the development of a downstream processing scheme for lysozyme recovery from NRL.